MENINGKATKAN KREATIVITAS SISWA DALAM MENGHIAS TAPLAK MEJA MELALUI METODE PEMBERIAN TUGAS DAN LATIHAN DI SMA N 4 PAYAKUMBUH - Johan, Erna; Ernawati, Ernawati; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2012)
Research Â to improve decorative student creativity [of] tablecloth [pass/through] method [gift/ giving] of practice and duty [in] SMA N 4 Payakumbuh.Kreativitas student in this research can be seen from four indicator that is: Feeling to like to know student siswa,keberanian, creating new ideas, getting new pengelaman in decorating tablecloth with application embroidery. Research type that is Research Of Action Class ( PTK) consist of II cycle. Research Subjek [is] student of SMAN 4 Payakumbuh, amounting to 20 student people in class development of executed [by] data collecting diri.Teknik [is] Observation and technique analyse quantitative data and qualitative Result of research indicate that student creativity [at] indicator: feel to like to know [at] cycle of I mean 54%, cycle of II 84%. Bravery [at] cycle of I mean 56%, cycle of II 88%. Creating new ideas [at] cycle of I mean 57%, cycle of II 87%, and get new experience [at] cycle of I mean 63%, cycle of II 85%. Becoming student creativity mean in decorating tablecloth with application embroidery with four indicator, cycle of I 59% categorized less and cycle of II 85% very well, student creativity bararti have been reached, with attainment goals which have been specified [by] that is 80%. Becoming with method [gift/ giving] of practice and duty in course of study can mount student creativity, in making application embroidery [at] tablecloth